2016
DOI: 10.1088/0957-4484/27/41/414005
|View full text |Cite
|
Sign up to set email alerts
|

The WS2quantum dot: preparation, characterization and its optical limiting effect in polymethylmethacrylate

Abstract: Due to the matching surface energy, WS2 quantum dots (QDs) can be obtained through direct liquid exfoliation in N-methyl-2-pyrrolidone rather than an ethanol and water mixture. Ultra-small WS2 QDs with a diameter of 2.4 nm are fabricated by an ultrasound method followed by high speed centrifugation up to 10 000 rpm. An excellent nonlinear optical (NLO) property of the WS2 QD/ polymethylmethacrylate (PMMA) composite for the nanosecond pulsed laser at both 532 and 1064 nm has been measured. Results illustrate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Figure O explains RF spectrum of mode locked bound‐state solitons where frequency difference between two peaks was 15.16 MHz with signal‐to‐noise ratio of fundamental repetition rate as 64‐dB. The interesting nonlinear optical property was reported in WS 2 QD/polymethylmethacrylate composite towards the nanosecond pulsed laser at 532 and 1064 nm measurements . The studies confirmed onset thresholds and optical limiting thresholds as 0.011 J cm −2 and 0.07 J cm −2 and 0.04 J cm −2 and 0.14 J cm −2 at 532 nm and 1064 nm as excitation wavelengths, respectively.…”
Section: Photonic Device Applicationsmentioning
confidence: 66%
See 1 more Smart Citation
“…Figure O explains RF spectrum of mode locked bound‐state solitons where frequency difference between two peaks was 15.16 MHz with signal‐to‐noise ratio of fundamental repetition rate as 64‐dB. The interesting nonlinear optical property was reported in WS 2 QD/polymethylmethacrylate composite towards the nanosecond pulsed laser at 532 and 1064 nm measurements . The studies confirmed onset thresholds and optical limiting thresholds as 0.011 J cm −2 and 0.07 J cm −2 and 0.04 J cm −2 and 0.14 J cm −2 at 532 nm and 1064 nm as excitation wavelengths, respectively.…”
Section: Photonic Device Applicationsmentioning
confidence: 66%
“…The luminescent MoS 2 nanocrystals was achieved by inexpensive and impurity free sono‐chemical exfoliation method followed by centrifugation . WS 2 QDs of average size around 2.4 nm were successfully synthesized using ultrasonication process with WS 2 powder and NMP solution under vigorous stirring for 15 h at 29 °C …”
Section: Fabrication Of 2d Qdsmentioning
confidence: 99%
“…Following the successful application of graphene, great attention has been paid to other layered inorganic graphene analogues due to their peculiar and fascinating physical properties that are correlated with their 2D ultrathin atomic layer structure. Transition metal dichalcogenides (TMDs) have attracted increasing attention in recent years due to their unique optical and electronic properties and have found many applications in catalysts, optoelectronics, and bio-imaging 14 . As the electronic band structure of semiconductor materials is relatively sensitive to the quantum size effect, layered TMDs exhibit excellent fluorescence properties when they are tailored into quantum dots (QDs) 58 .…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional transition-metal dichalcogenides (TMDCs) have been applied in fluorescent imaging [11], biological sensing [12], and photocatalytic [13] due to their unique optoelectronic properties. Tin diselenide (SnSe 2 ) is a semiconductor in the TMDCs family.…”
Section: Introductionmentioning
confidence: 99%